Determinants of smallholder crop farmers’ access to climate services in Elundini local municipality, Eastern Cape province, South Africa - Nocezo, Yanga-Inkosi; Manyike, Jabulile Zamokuhle; Zhou, Leocadia; Ngarava, Saul (Frontiers in Climate, 2024)
Climate variability presents significant implications for agricultural production and overall food security, leading to seeking better access to climate services that can improve farmers’ decision-making in combating climate change impacts. The study examined the factors influencing smallholder crop farmers’ access to climate services in Elundini local municipality, Eastern Cape province. The study adopted a quantitative method using a cross-sectional survey approach. A multistage sampling procedure was employed to select 217 smallholder crop farmers. The study used primary data collected through structured questionnaires and face-to-face interviews. To analyze the data the paper employed a binary Probit model. The study results indicated that access to both short-term weather and seasonal forecasts is positively influenced by ownership of mobile phones and access to extension services. Similarly, access to short-term weather forecasts is positively influenced by age, monthly income, ownership of radio, timely climate information, and perceiving that climate change has negative effects on crop production. The study further revealed that land size, knowledge of climate change, and climate services accuracy are positive and significant factors in access to seasonal forecasts. On the other hand, being educated negatively influenced access to seasonal forecasts while land size had a negative and significant effect on short-term weather forecasts. The study concludes that age, land size, ownership of mobile phones, and access to extension services were significant factors that determine both farmers’ access to short-term weather and seasonal forecasts. Therefore, the study recommends that if the access and uptake of climate services are to be improved, government stakeholders, researchers, and forecast producers should collaborate and offer training sessions and workshops on climate services relevance and how to acquire and interpret them, particularly for elderly farmers.